Peningkatan Kualitas Prinsip Manajemen Perusahaan Perkebunan Yang Terdaftar Di Bursa Efek Indonesia Melalui Laporan Arus Kas Terhadap Return Saham - Flora Silalahi; Asri Sanusi; Juli Meliza (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
One of the economic indicators in a country is the capital market. Indonesia is one of the countries where the capital market is developing, this is proven by the number of companies listing in the capital market. One of the advantages of capital market activities is stock returns. Stock Return is the income earned by investors for investing funds in the form of shares. This study aims to determine how the effect of cash flow statements on stock returns. As for the object of scrutiny is PT. Astra Agro Lestari Tbk, PT. London Sumatra Indonesia Tbk, PT. Jaya Agra Wattie Tbk. In this study, the indicators used by the authors are cash flow statements from operational activities, investment activities and financing activities. The results showed that partially and simultaneously there is an influence between cash flow on stock returns. Based on the results of research conducted with the t-test, the results obtained that the value of tcount > ttable so that it shows there is an influence between the independent variables on the dependent variable, for the r-test shows that the operational cash flow variable has a moderate effect, the investment cash flow variable has a moderate influence. very low and the funding cash flow variable has a low influence on stock returns. Meanwhile, for the f test, the results obtained that the value of Fcount > Ftable so that it shows that there is an influence between the independent variables on the dependent variable. And for the R2 test, the results obtained are 44% (0.444 x 100%).